BUSINESS INTELLIGENCE BERBASIS WEB (STUDY KASUS SEPATU SANDAL (Information Technology and Telematics, 2015)
Abstract – Sofiy Shoes is one of the businesses in trade shoes. Sofiy Shoes has not had the media to promote its products widely to the public. The existing system in Sofiy Shoes still manually or models still recording in the book. To overcome this created a web-based Intelligent Business applications that can give information to companies in order to produce a decision. This application is implemented as a tool to grow your business to the public Sofiy Shoes by adjusting its products with a product that is a trend or favored by the public. The system development method used in this study is a waterfall. The design of the system using DFD consisting of context diagram, DFD Level 0, DFD Level 1, Level 2 DFD and ERD. Making a website using PHP and using MySQL database. Currently Shoes Sofiy applications already using the domain http://sofiyshoes.16mb.com address so as to increase consumer confidence to perform. Keywords-Business Intelligence, Shoes, Shoes Sofiy